Remoção de íons metálicos de efluentes utilizando bentonitas e diatomita tratadas com microemulsões - Borges, Valdivino Francisco dos Santos (2018)
Heavy metals have been contributing significantly to water pollution, interfering temporarily or permanently in the maintenance of aquatic biota. Industrial development contributes to water pollution by contaminating rivers, lakes and seas with heavy metals. The use of natural and chemically treated adsorbents has been an alternative in the capture of metallic ions present in aquatic environments through the adsorption process. The objective of this work was to evaluate the adsorption capacity of iron, lead and chromium ions present in synthetic solutions using commercial bentonite, sodium bentonite and diatomite in their natural forms and treated with micellar solution and microemulsion. The surfactant studied was Ultrol L-90, which together with n-butanol, kerosene and distilled water obtained a formulation consisting of direct micelle. After the treatment of the natural adsorbents with micellar solution and microemulsion, the characterizations were made by the techniques of X-ray Fluorescence (XRF), X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), N2 adsorption specific área (BET), Differential and Thermogravimetric Thermal Analysis (DTA/TGA) and Fourier Transform Infrared Spectroscopy (FTIR). The adsorption study of the metals showed that the treatment with the micellar solution does not modify the capture capability, being the efficiency almost equal to the natural adsorbents. While the treatment with the microemulsion significantly increases the percentage of adsorption efficiency, reaching 99% for iron and lead ions, and 83% for the chromium ion when the diatomite is present.